Brown recluse spider envenomation with systemic loxoscelism and delayed hemolysis: A case report. (15th January 2023) - DiPaola, Blake; Davis, Jason; Baum, Regan A.; Akpunonu, Peter; Micciche, Andrew
Abstract: The brown recluse spider (Loxosceles reclusa) is endemic to the South, West and Central Midwestern United States, and envenomation from this spider can cause cutaneous and/or systemic symptoms. We present a case of systemic loxocelism in an adolescent male resulting in three emergency department visits and two hospitalizations for a rare case of delayed hemolysis 6 days after envenomation. A 19-year-old male presented to the emergency department twice within two days after envenomation with worsening pain, subjective fever, chills, nausea and vomiting. He required a two-day hospitalization for rhabdomyolysis and acute kidney injury. The patient was discharged with improving symptoms and laboratory results on day four before returning again on day seven with worsening symptoms. He was diagnosed with hemolytic anemia on day seven and was subsequently hospitalized for six days. This case of systemic loxoscelism manifested hemolysis six days after envenomation, following an improvement in symptoms and laboratory studies. This case highlights the need for continuous monitoring and/or follow-up in cases of systemic loxocelism. Graphical abstract: Image 1 Highlights: Brown recluse spider bites can produce local and systemic symptoms. Our patient presented initially with localized ecchymosis and swelling. He subsequently developed systemic loxoscelism and very delayed hemolysis. Hemolysis in this patient occurred much later than is typical. Patients may need to be monitored for hemolysis longer than traditionally thought.